Chemically reduced graphene oxide-reinforced poly(lactic acid)/poly(ethylene glycol) nanocomposites: preparation, characterization, and applications in electromagnetic interference shielding - Ahmad, Ahmad Fahad; Ab. Aziz, Sidek; Abbas, Zulkifly; Obaiys, Suzan Jabbar; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz; Raad, Haider K.; Aliyu, Umar Sa'ad (MDPI, 2019)
In this study, a nanocomposite of reduced graphene oxide (RGO) nanofiller-reinforcement poly(lactic acid) (PLA)/poly(ethylene glycol) (PEG) matrix was prepared via the melt blending method. The flexibility of PLA was improved by blending the polymer with a PEG plasticizer as a second polymer. To enhance the electromagnetic interference shielding properties of the nanocomposite, different RGO wt % were combined with the PLA/PEG blend. Using Fourier-transform infrared (FT-IR) spectroscopy, field emission scanning electron microscopy (FE-SEM) and X-ray diffraction, the structural, microstructure, and morphological properties of the polymer and the RGO/PLA/PEG nanocomposites were examined. These studies showed that the RGO addition did not considerably affect the crystallinity of the resulting nanomaterials. Thermal analysis (TGA) reveals that the addition of RGO highly improved the thermal stability of PLA/PEG nanocomposites. The dielectric properties and electromagnetic interference shielding effectiveness of the synthesized nanocomposites were calculated and showed a higher SE total value than the target value (20 dB). On the other hand, the results showed an increased power loss by increasing the frequency and conversely decreased with an increased percentage of filler.